Switching gas permeation through smart membranes by external stimuli: a review. Issue 32 (21st July 2022) - Widakdo, Januar; Austria, Hannah Faye M.; Subrahmanya, T. M.; Suharyadi, Edi; Hung, Wei-Song; Wang, Chih-Feng; Hu, Chien-Chieh; Lee, Kueir-Rarn; Lai, Juin-Yih
Abstract : Design strategies of smart membranes for switchable gas separation performance. Abstract : The gas separation process is one of the essential operations in refineries and gas-related industries. Recently, much effort has been dedicated to further modifying the gas separation properties of existing polymers further to expand their use for broad industrial gas separation applications. In recent years, gas permeation transfer through smart membranes has attracted attention for its ability to change properties when exposed to external stimuli, making it useful for gas separation applications. Electric, magnetic fields, light, temperature, pressure, and humidity are attractive triggers for responsive materials due to their fast, non-invasive properties and potential to significantly reduce energy costs. This review includes a discussion of the mechanism, and working system of several membranes studied to respond to external stimuli. Several studies that have been combined into this review article are expected to be a benchmark for future researchers who will explore membranes with various stimuli. More importantly, the readers can know and study the phenomenon behind the separation capabilities of intelligent membranes.